Legal Protection of Creditors in Credit Agreements with Liability Guarantee - Siti Nurjanah; Teuku Syahrul Ansari; Bambang Daru (IHSA Institute, 2022)
Credit generally functions to facilitate business activity and, especially for economic activities in Indonesia, plays a vital role in its position both for production businesses and private businesses that are developed independently because they aim to improve the community's standard of living. Banks as financial institutions that produce financial services that have helped fulfill the need for funds for economic activities by providing loans, among others through bank credit, in the form of credit agreements between creditors as lenders or credit facilities with debtors as debtors. The problem is raised in legal protection for creditors when the debtor defaults and what sanctions the creditor gives when the debtor defaults. The aim is to find out the legal guardian for creditors in credit agreements and what sanctions are given by creditors when the debtor defaults. This study uses quantitative methods, namely methods based on the philosophy of positivism. This method is used to examine a particular population or sample. Sampling techniques are generally carried out by random (data collection). Creditors obtain legal protection when the debtor defaults by Article 51 of Law Number 5 of 1960 and Law no. 4 of 1996. The creditor can impose sanctions on the debtor when the debtor defaults in Article 20 paragraph (1) of the Mortgage Law. The result of this research is that a vital guarantee right institution has been provided and can be charged to land rights, namely Mortgage Rights as a substitute for the Hypotheek and Credit Verband Institutions. For this reason, I suggest to readers in particular and society in general that we should follow the existing and applicable laws and regulations in Indonesia every time we take action.